The Impact of the Great Recession on Emerging Markets - Salman, Ferhan (IMF Working Papers; Working Paper ;, 2010)
This paper examines the impact of the recent global crisis on emerging market economies (EMs). Our cross-country analysis shows that the impact of the crisis was more pronounced in those EMs that had initial weaker fundamentals and greater financial and trade linkages. This effect is observed along a number of dimensions, such as growth, stock market performance, sovereign spreads, and credit growth. This paper also shows that during this crisis, pre-crisis reserve holdings helped to mitigate the initial growth collapse. This finding contrasts with other studies that fail to find a significant relationship between reserves and the growth decline. This paper argues that our preferred measure of impact is a more accurate reflection of the true impact of the crisis on EMs.